Anul 1918 în istoria Catedrei de limba română de la Universitatea din Budapesta (Romanian Studies Today, 2024)
The year 1918 finds the Department of Romanian from the University of Budapest engaged in a fight for leadership, a fight that had commenced to a certain extent after the death of its founder, Alexandru Roman. Ioan Ciocan, Iosif Siegescu, and Gheorghe Alexici were the main contenders for the leading position of the Department of Romanian. Each of the three has remained in the history of the department or in the memory of their successors with the light and shadows of their activities. Ioan Ciocan’s name, the editor of Albina journal, has earned recognition due to the monograph on the history of Romanian orthography, but also due to the collection of texts written for the Romanian soldiers fighting in World War I, while Gheorghe Alexici distinguished himself by his research on folklore.
Keywords: 1918; Romanian Department from the University of Budapest; Ioan Ciocan; Iosif Siegescu; Gheorghe Alexici